Why Are Children With Bronchiolitis At Risk Of Urinary Tract Infections? - Hendaus MA (Dove Medical Press, 2019)
Mohamed A Hendaus1,2 1Department of Pediatrics, Section of Academic General Pediatrics, Sidra Medicine, Doha, Qatar; 2Department of Clinical Pediatrics, Weill- Cornell Medicine, Doha, QatarCorrespondence: Mohamed A HendausDepartment of Pediatrics, Sidra Medicine, Doha 26999, QatarTel +974-4003-6559Email mhendaus@yahoo.comAbstract: Viral respiratory infections are frequently eliminated from human bodies without any sequelae. Secondary serious bacterial infection (SBI) in children with acute bronchiolitis has been an apprehension expressed by health care providers. Several published studies have shown an association between acute bronchiolitis and secondary bacterial infection, including urinary tract infections (UTI). However, the proposed mechanism by which a virus can induce UTIs is not yet known. The aim of this commentary is to update the current evidence of risk of UTI in children with bronchiolitis. We present several clinical studies related to the topic as well as a brief review of the potential pathophysiology of secondary infections that could present with viral respiratory illness.Keywords: bronchiolitis, infection, urine